Analisis Pengaruh Tingkat Pengangguran Indeks Pembangunan Manusia, dan Upah Minimum Terhadap Jumlah Penduduk Miskin di Kota Serang Tahun 2018-2023 - Dewi, Shafa Salsabila; Rahmadani, Dhia Zalfa Dwi; Perthami, Perthami; Desmawan, Deris (Jurnal Informatika, 2024)
In this research, the expected objective is to determine the distribution, classification and level of unemployment, human development index, minimum wage and the number of poor people in Serang City in 2018-2023. This research uses a multiple analysis model, using SPSS version 25. The regression results show that the HDI variable on the Number of Poor Population has a negative effect, namely decreasing by 0.950 and is statistically significant with the unemployment rate and minimum wage.